THE PRINCIPLE OF LEGALITY IN CIVIL PROCEEDINGS - Gharslyan, Ashkhen (State and Law, 2021)
In this article, the author examines the features of the manifestation of the principle of legality in civil proceedings. In particular, the author considered this principle of both the organizational-functional and functional principle of civil proceedings. As a result of the study, the author came to the conclusion that the essence of the principle of legality is that justice should be administered by a court created on the basis of the law, and should be conducted in compliance with the requirements of substantive and procedural law by the court and other participants in the trial.
Keywords: legality; principle; court; created on the basis of the law; legal norm; human rights and freedoms; normative legal acts